(untitled) (Configurazioni. Research on contemporary poetry, 2023)
This paper aims to investigate the specific dynamics and circuits of poetic valorization in the latter half of the Twentieth century, assuming that the condition of ‘resistant marginality’ of the poetry genre in contemporary societies is pragmatically correlated with the peculiar relationships established between poetic communities and literary communities. Within this framework, the circuits of poetry publishing can be observed as a complex system of selective valorization of works and authors: in the critical examination of its functioning, distant reading tools can offer a valuable resource, not as an alternative but as a complement to the close study of individual authors, publishing series, journals. The paper tests the potential of this perspective through some initial experiments or partial surveys: in particular, it proposes a comparison between the catalog choices of the three major contemporary Italian poetry series (Mondadori’s Lo Specchio, Garzanti’s Verde, Einaudi’s Bianca) and the variously “canonical” selections proposed from a sample of influential anthologies.